Proposing the use of partial AUC as an adjunctive measure in establishing bioequivalence between deltoid and gluteal administration of long-acting injectable antipsychotics - Lee, Lik Hang N.; Choi, Charles; Gershkovich, Pavel; Barr, Alasdair M.; Honer, William G.; Procyshyn, Ric M. (Springer, 2016)
The maximum plasma concentration (Cmax) and the area under the plasma concentration–time curve (AUC) are commonly used to establish bioequivalence between two formulations of the same oral medication. Similarly, these pharmacokinetic parameters have also been used to establish bioequivalence between two sites of administration for the same injectable formulation. However, these conventional methods of establishing bioequivalence are of limited use when comparing modified-release formulations of a drug, particularly those with rates of absorption that are amenable to change with the site of injection. Inherent differences in the rate of absorption can result in clinically significant differences in early exposure and drug response. Here, we propose the use of the partial AUC (pAUC) as a measure of early exposure to aid in the assessment of bioequivalence between the gluteal and the deltoid site of administration for long-acting injectable antipsychotics.